2020
DOI: 10.3389/fonc.2020.568557
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Cancer Associated Fibroblasts and Cancer Cells in Scirrhous Type Gastric Cancer

Abstract: Gastric cancer (GC) is the third leading cause among all cancer deaths globally. Although the treatment outcome of GC has improved, the survival of patients with GC at stages III and IV remains unsatisfactory. Among several types of GC, scirrhous type GC (SGC) shows highly aggressive growth and invasive activity, leading to frequent peritoneal metastasis. SGC is well known to accompany abundant stromal cells that compose the tumor microenvironment (TME) along with the produced extracellular matrix (ECM) and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 121 publications
2
30
0
Order By: Relevance
“…Although the involvement of SHP2 in hematogenous metastasis has been reported in several cancer types [52][53][54], this is the first study to demonstrate the importance of SHP2 in peritoneal dissemination. DGC cells dispersed in the abdominal cavity must attach to and migrate across the mesothelium, invade the underlying stroma, and regrow to form peritoneal tumors [23,55,56]. Based on our results, SHP2 is likely to participate in the migration, invasion, and growth of DGC cells during peritoneal dissemination.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although the involvement of SHP2 in hematogenous metastasis has been reported in several cancer types [52][53][54], this is the first study to demonstrate the importance of SHP2 in peritoneal dissemination. DGC cells dispersed in the abdominal cavity must attach to and migrate across the mesothelium, invade the underlying stroma, and regrow to form peritoneal tumors [23,55,56]. Based on our results, SHP2 is likely to participate in the migration, invasion, and growth of DGC cells during peritoneal dissemination.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, Met and FGFR2 were proposed as potential therapeutic targets for DGC [16,17]. Indeed, other groups and we demonstrated that Met and FGFR inhibitors have therapeutic efficacy in preclinical models [18][19][20][21][22]; as a result, some of them were tested in clinical trials [23]. However, acquired resistance to Met and FGFR inhibitors inevitably occurs in DGC [22,24], which will be problematic in clinical practice.…”
Section: Introductionmentioning
confidence: 94%
“…To our knowledge, we are the first to point out CAF infiltration is higher in DGC and GS tumor that both are poorer survival subtypes in their corresponding classification system [ 25 , 28 ]. This difference might be explained by the overlapping of DGC and GS with scirrhous gastric cancer characterized as rapid expansion and invasion of poorly differentiated or signet‐ring cancer cells with extremely surrounding fibrosis [ 48 ]. Our result also reveals CAF infiltration is generally higher in stage III and IV patients implying the involvement of CAF in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…DGC is characterized by rapid invasive growth and frequent peritoneal dissemination. The process of peritoneal dissemination includes attachment of DGC cells to the mesothelium, invasion into the submesothelial connective tissue, and subsequent growth to form tumors 33 , 34 . Our results demonstrate that PLEKHA5 silencing markedly blocked the peritoneal dissemination of DGC cells.…”
Section: Discussionmentioning
confidence: 99%